Geographic Variation in Antibiotic Consumption-Is It Due to Doctors' Prescribing or Patients' Consulting? - Marte Meyer Walle-Hansen; Sigurd Høye (MDPI AG, 2018)
Antibiotic consumption varies greatly between Norwegian municipalities. We examine whether this variation is associated with inhabitants' consultation rates or general practitioners' (GP) prescription rates. Our study comprises consultations and antibiotic prescriptions for respiratory tract infections (RTIs) in general practice in all Norwegian municipalities with over 5000 inhabitants in 2014. Data was collected from The Norwegian Prescription Database, The Directorate of Health's system for control and payment of health reimbursements registry and Norway Statistics. Consultation rates and prescription rates were categorised in age- and gender specific quintiles and the effect on antibiotic consumption was analysed using a Poisson regression model. We found that inhabitants with RTIs received 42% more prescriptions if they belonged to a municipality with high consultation rates compared to low consultation rates [incidence rate ratio (IRR) 1.42 (95% CI 1.41-1.44)] and 48% more prescriptions if they belonged to a municipality with high prescription rates versus low prescription rates [IRR 1.48 (95% KI 1.47-1.50)]. Our results demonstrate that inhabitants' consultation rates and GPs' prescription rates have about equal impact on the number of RTI antibiotics prescribed at municipality level. These findings highlight the importance of interventions targeting patients as well as doctors in efforts to reduce unnecessary antibiotic consumption.